Road map towards improved Afghan public sector wheat basic research capacity and performance - CGIAR Research Program on Wheat (2021)
the document lists existing structure and resources of the Agricultural Research Institute of Afghanistan and identifies gaps and requirements for an efficient delivering breeding programme in Afghanistan.